Design and Implementation of Guidance System for Visually Impaired People - Alshahri, S.S. (Institute of Electrical and Electronics Engineers Inc., 2021)
As per the World Health Organization (WHO) statistics, there are there are 285 million visually disabled people worldwide, of whom 39 million are completely blind. To help those blind people and improve their lives quality, several systems have been developed including the guidance systems. The guidance systems are essential to assist and monitor the location of visually impaired people. Therefore, this paper aims to design and develop a guidance system with self-administered approach to help the blind people practicing their normal life. In the proposed system, a wearable vest is used to help the bind people avoid obstacles or any risk during walking. The ultrasonic sensors are attached to the vest, which blind people wear to detect the object. In addition to detecting the objects, the proposed system uses GPS system and GSM module to monitor the location of the visually disabled people. The system alerts the user if there is an obstacle by vibrating, and if the user gets closer the second alert will be a voice warning to tell the visually impaired user where the obstacle is (e.g., left, or right side). The experimental results show that the proposed system can detect objects accurately that are 120 cm away and trigger a real time alert to allow the blind person to respond quickly. Â© 2021 IEEE.